EFL STUDENTS’ EXPERIENCE OF PICTURE SERIES COLLABORATIVE NARRATIVE WRITING: HIGHLIGHTING INDONESIAN VOCATIONAL HIGH SCHOOL STUDENTS’ VOICE - Fasikha Al-Izhar; Chubbi Millatina Rokhuma (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
In education research, positive attention has been paid to the role of picture series collaborative writing methods to improve students’ writing achievement. To fill this gap, the present study applied the approach of narrative inquiry and explored how students experience collaborative narrative writing activity. Six graders from a vocational school in Central Java, Indonesia participated in this study. Data were collected through semi-structured interviews. For analyzing the data, the researcher employed thematic analysis by Brown and Clarke (2006). The result of this study showed that there were different perspectives for each participant in how they write narrative text through picture series collaboration. The finding can be a consideration for teachers who will use this media for teaching.